2002
DOI: 10.2458/azu_jrm_v55i2_west
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation responses following wildfire on grazed and ungrazed sagebrush semi-desert

Abstract: A 20-year set of cover data on sagebrush semi-desert plant communities responding to wildfire and livestock grazing near Mills in central Utah provided an opportunity to compare the assumptions and adaptability of classical and state-and-transition models for describing secondary succession. Cover data were organized and analyzed by plant species, growth forms, and other ground cover classes. Graphical analysis, ordination (employing semi-strong hybrid multi-dimensional scaling), regression, and analysis-of-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 7 publications
1
43
0
Order By: Relevance
“…Moderate grazing after perennial grass dormancy (that is, late season) in the first two summers after fire is not likely to reduce the recovery ability of herbaceous communities in sagebrush-steppe (Bates and others, 2009) when rest during the growing season is permitted. Differences in herbaceous cover among burn-ungrazed and burn-grazed areas were not observed during the first 6 years after fire, but between 7 and 18 years post-fire, perennial grass cover in grazed areas was less than cover in ungrazed areas (West and Yorks, 2002), so long-term post-treatment monitoring may be important. Treated areas may draw grazing pressure from all herbivores; thus, treatment designs that consider the possibility of an unplanned escalation of use by wild horses or elk (Cagney and others, 2010) when significant populations of these species are present have better chances of meeting productivity and habitat targets.…”
Section: A9 Grazingmentioning
confidence: 99%
See 4 more Smart Citations
“…Moderate grazing after perennial grass dormancy (that is, late season) in the first two summers after fire is not likely to reduce the recovery ability of herbaceous communities in sagebrush-steppe (Bates and others, 2009) when rest during the growing season is permitted. Differences in herbaceous cover among burn-ungrazed and burn-grazed areas were not observed during the first 6 years after fire, but between 7 and 18 years post-fire, perennial grass cover in grazed areas was less than cover in ungrazed areas (West and Yorks, 2002), so long-term post-treatment monitoring may be important. Treated areas may draw grazing pressure from all herbivores; thus, treatment designs that consider the possibility of an unplanned escalation of use by wild horses or elk (Cagney and others, 2010) when significant populations of these species are present have better chances of meeting productivity and habitat targets.…”
Section: A9 Grazingmentioning
confidence: 99%
“…As this optimal colonist species established, chronic grazing by cattle, sheep, and horses combined with drought and fire to increase the distribution and frequency of disturbance and further optimize this region for dominance by an annual grass (Knapp, 1996). Importantly, research in sagebrush ecosystems has revealed an inverse relation between cheatgrass dominance and native perennial herbs, especially grasses (West and Yorks, 2002). Further, the post-disturbance response of sagebrush communities to fire and similar disturbances is strongly affected by the condition and composition before disturbance, the presence of propagules, and sprouting of native species (West and Yorks, 2002;Beck and others, 2009;Epanchin-Niell and others, 2009;Condon and others, 2011).…”
Section: A7 Invasive Plantsmentioning
confidence: 99%
See 3 more Smart Citations